THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN EMPLOYEE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW AT XYZ UNIVERSITY - Zahara Tussoleha Rony; Didi Rochyadi Mangkupradja; Pramukty, Rachmat (ZILLZELL MEDIA PRIMA, 2023)
Transformational leadership has become an important subject of research in the field of management and organizational psychology, due to its powerful influence on individual and group performance. The method used in this study is the search for scientific articles in leading academic databases. Inclusion criteria were established to select articles relevant to this research topic, i.e. research explaining the relationship between transformational leadership and employee performance at XYZ University. After passing the selection process, articles that meet the inclusion criteria are taken as research samples. The results of this systematic literature review show that transformational leadership has a significant positive impact on employee performance at XYZ University. Several studies have found that transformational leadership is positively associated with productivity, work quality, job satisfaction, and employee organizational commitment. Previous research has shown that transformational leadership affects employee performance through several mechanisms. First, transformational leadership encourages employees to adopt a strong organizational vision, which provides clear goals and direction. Second, transformational leadership creates a work environment that supports employees' personal and professional development, which increases their motivation and commitment to the organization. Third, transformational leadership builds strong interpersonal relationships between leaders and employees, which improves trust, communication, and collaboration. In addition, this literature review also identified several contextual factors that can moderate the relationship between transformational leadership and employee performance. These factors include organizational culture, organizational structure, and individual characteristics of employees. In an organizational culture that supports innovation and participation, transformational leadership can have a stronger impact on employee performance. Similarly, flexible and empowering organizational structures can enhance the effects of transformational leadership on employee performance. In addition, individual characteristics such as motivation and personality can also influence the relationship between transformational leadership and employee performance. The findings of this study show that transformational leadership has an important role in improving employee performance. Organizations need to understand the importance of transformational leadership and apply it in their context to improve employee productivity and success. However, more research is needed to understand more deeply the mechanisms and contextual factors that influence these relationships, as well as test their effects in different organizational contexts.